2021
DOI: 10.1177/23259671211005090
|View full text |Cite
|
Sign up to set email alerts
|

Decision Making for Treatment After ACL Injury From an Orthopaedic Surgeon and Patient Perspective: Results From the NACOX Study

Abstract: Background: In the treatment of anterior cruciate ligament (ACL) injuries, there is little evidence of when and why a decision for ACL reconstruction (ACLR) or nonoperative treatment (non-ACLR) is made. Purpose: To (1) describe the key characteristics of ACL injury treatment decisions and (2) compare patient-reported knee instability, function, and preinjury activity level between patients with non-ACLR and ACLR treatment decisions. Study Design: Cohort study; Level of evidence, 2. Methods: A total of 216 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 33 publications
0
14
1
Order By: Relevance
“…Some patients and clinicians made a shared decision to undergo early ACLR within 3 months from injury. 30 The main reasons for nonsurgical treatment were “no knee instability” and “no problems with knee function.” 30 The main reason for undergoing early ACLR (within 31 days of injury) was “high activity demands.” 30 In the subacute phase (32 days to 5 months after injury), “instability/giving way” and high-activity demands were the main reasons for undergoing ACLR, and a later ACLR decision was most often due to instability/giving way. 30 …”
Section: Methodsmentioning
confidence: 99%
“…Some patients and clinicians made a shared decision to undergo early ACLR within 3 months from injury. 30 The main reasons for nonsurgical treatment were “no knee instability” and “no problems with knee function.” 30 The main reason for undergoing early ACLR (within 31 days of injury) was “high activity demands.” 30 In the subacute phase (32 days to 5 months after injury), “instability/giving way” and high-activity demands were the main reasons for undergoing ACLR, and a later ACLR decision was most often due to instability/giving way. 30 …”
Section: Methodsmentioning
confidence: 99%
“…However, there was a high number of responses stating that the physiotherapist or orthopaedic surgeon was not involved in the decision. Previous research has shown that the orthopaedic surgeon might not always be involved in a non-ACLR decision [ 8 ], and perhaps a physiotherapist is not always involved when an early decision for ACLR is taken. In contrast, orthopaedic surgeons and physiotherapists do state that they rate the importance of each other’s assessments highly [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are some studies of patients’ perspectives regarding choice of treatment after an ACL injury [ 7 , 8 , 19 , 20 ], but to the authors´ knowledge, studies on a decision-making process that involves the perspectives of the patient, the orthopaedic surgeon and the physiotherapist are lacking. Hence, in order to provide evidence-based care and shared decision-making about the choice of treatment for patients with an ACL injury, we need to further investigate how the treatment decision-making process is experienced by patients, orthopaedic surgeons and physiotherapists.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 An ACL reconstruction is recommended in patients who intend to return to high-level sports. 3,4 However, previous studies demonstrated that only 55e80% of patients return to the pre-injury level of sports. 5,6 Furthermore, a re-injury rate up to 20% is observed in young and active patients.…”
Section: Introductionmentioning
confidence: 99%